Sovereignty and the utilitas calamitatis - Pranger, M. Burcht (Augustinian studies, 2025)
Point of departure is the way post-modern philosophers such as Judith Butler and Giorgio Agamben have theorized the calamity of 9/11. What comes to the fore is a Carl Schmitt-like preoccupation with foundational notions like Setzung - notions that in their turn are embedded in a web of negativity, culminating in the sovereign status, for good or for ill, of the state of exception. Next, we turn to Augustine's way of dealing with disaster in De civitate dei. If there is any foundational dimension to be found in De civitate, it is in the Augustinian concept of permixtio, the entanglement of the two cities. This very permixtio functions as a razor cutting off each and every attempt to hypostatize negativity or to establish sovereignty reaching beyond the dynamics of the cursus of the entangled cities. As a result, the meaning of disaster (the utilitas calamitatis) should be assessed within the parameters of that entanglement. Thus the destruction of Carthage as alerting the reader semantically to historical catastrophe, becomes entangled in a more serious calamity resulting, not from historical disaster but from the failure to cope with victory which in the end comes down to the failure to cope with oneself.